2001
DOI: 10.1126/science.1060786
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Catalyzed RNA Polymerization: Accurate and General RNA-Templated Primer Extension

Abstract: The RNA world hypothesis regarding the early evolution of life relies on the premise that some RNA sequences can catalyze RNA replication. In support of this conjecture, we describe here an RNA molecule that catalyzes the type of polymerization needed for RNA replication. The ribozyme uses nucleoside triphosphates and the coding information of an RNA template to extend an RNA primer by the successive addition of up to 14 nucleotides-more than a complete turn of an RNA helix. Its polymerization activity is gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
596
2
11

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 685 publications
(616 citation statements)
references
References 28 publications
7
596
2
11
Order By: Relevance
“…While there is no evidence supporting the specific metal contacts required by the two-metal-ion mechanism for the ligase reaction, there are several parallels between reactions catalyzed by the ligase ribozyme and proteinaceous polymerases that are consistent with this mechanism. The ligase, which forms the catalytic core of an RNA polymerase ribozyme, has the same stereochemical preference for sulfur substitution at the R-phosphate as polymerases composed of protein (20,21), and both the ligase and polymerases made of protein can tolerate only Mg 2+ or Mn 2+ at their active sites (30). In addition, kinetic and structural analysis in the presence of Mg 2+ and Ca 2+ suggested that the ligase may require two metal ions for catalysis.…”
Section: Role Of Metal Ions In Structure Andmentioning
confidence: 99%
“…While there is no evidence supporting the specific metal contacts required by the two-metal-ion mechanism for the ligase reaction, there are several parallels between reactions catalyzed by the ligase ribozyme and proteinaceous polymerases that are consistent with this mechanism. The ligase, which forms the catalytic core of an RNA polymerase ribozyme, has the same stereochemical preference for sulfur substitution at the R-phosphate as polymerases composed of protein (20,21), and both the ligase and polymerases made of protein can tolerate only Mg 2+ or Mn 2+ at their active sites (30). In addition, kinetic and structural analysis in the presence of Mg 2+ and Ca 2+ suggested that the ligase may require two metal ions for catalysis.…”
Section: Role Of Metal Ions In Structure Andmentioning
confidence: 99%
“…It seems very reasonable to assume that some random RNA 175 molecules -or an assembly of a few different ones -generated on the mineral surface might have 176 had a weak RNA-replicase activity. This would have been sufficient to ignite the selection process 177 for a gradual increase of replicase activity (Attwater et al 2010; Johnson et al 2001). The snag with 178 this straightforward reasoning is empirical: even though RNA replicase ribozymes are actively 179 searched for in many laboratories (Johnson et al 2001 differentially, then the number of potentially coexistent replicators is equal to the number of 202 monomer pairs (two in this case: A+U and C+G, (Szilágyi et al 2013)).…”
mentioning
confidence: 99%
“…This would have been sufficient to ignite the selection process 177 for a gradual increase of replicase activity (Attwater et al 2010; Johnson et al 2001). The snag with 178 this straightforward reasoning is empirical: even though RNA replicase ribozymes are actively 179 searched for in many laboratories (Johnson et al 2001 differentially, then the number of potentially coexistent replicators is equal to the number of 202 monomer pairs (two in this case: A+U and C+G, (Szilágyi et al 2013)). Since the differential use of 203 monomers by the replicators -i.e., a marked difference in their A+U and C+G demand -would 204 represent a severe constraint on their function (replicase activity), it seems reasonable to assume 205 that the monomer pool constitutes a single resource, which implies a single winner.…”
mentioning
confidence: 99%
“…In this RNA World scenario [117,116], the translation of RNA into proteins and, finally, the usage of DNA [110] as information storage device are later innovations. The wide range of catalytic activities that can be realized by relatively small ribozymes [22,177,188,191,236,411] as well as the usage of RNA catalysis at crucial points of the information metabolism of modern cells [186,86,289] provides support for the RNA World hypothesis. Plausible ribozyme catalyzed pathways for a late-stage ribo-organism [191], the role and evolution of co-enzymes [180], and a rather detailed model of the steps leading from the RNA world to modern cellular architectures [333] have been the subject of detailed investigations.…”
Section: Introductionmentioning
confidence: 95%